Telomeres and telomerase in oncogenesis - Kowalska, Aldona; Kowalik, Artur (Contemporary Oncology/Współczesna Onkologia, 2006)
The telomere is a structural and functional entity that is present on the ends of chromosomes. In the past few years the significance of telomeres and telomerase in neoplasia has grown due to better understanding of their structure and function. In the process of oncogenesis telomeres act as tumour suppressors. Disturbance of their function and deregulation of telomerase activity are important factors for oncogenesis. The present knowledge about telomerase and telomeres allows for designing drugs and therapeutic schemes useful in cancer. Composite tissue cultures useful for transplantology have also been developed. Studies on telomeres and telomerase are developing dynamically and surely the last word has not been said.